Genetic characteristics of the HeLa cell. - Hsu, S; Schacter, B; Delaney, N; Miller, T; McKusick, V; Kennett, R; Bodmer, J; Young, D; Bodmer, W (1976)
The genotype of the patient Henrietta Lacks from whose cervical carcinoma the HeLa cell was derived was deduced from the phenotypes of her husband and children, and from studies of the HeLa cell. Hemizygous expression of glucose-6-phosphate dehydrogenase in HeLa, together with the deduced heterozygosity of Mrs. Lacks, is consistent with clonal origin of her neoplasm.